PI(4)P homeostasis: Who controls the controllers?. (January 2016) - Venditti, Rossella; Masone, Maria Chiara; Wilson, Cathal; De Matteis, Maria Antonietta
Abstract: During recent decades, PI(4)P (phosphoinositol-4-phosphate) has been described as a key regulator of a wide range of cellular functions such as organelle biogenesis, lipid metabolism and distribution, membrane trafficking, ion channels, pumps, and transporter activities. In this review we will focus on the multiple mechanisms that regulate PI(4)P homeostasis ranging from those responsible for the spatial distribution of the PI4 kinases and PI(4)P phosphatase to those controlling their enzymatic activity or the delivery/presentation of the substrate, i.e. PI or PI(4)P, to the PI4Ks or PI(4)P phosphatase, respectively. We will also highlight the open questions in the field mainly dealing with the existence and mode of action of PI(4)P sensors that monitor its amount and can act as a rheostat tuning PI(4)P levels in different compartments and adapting them to the different needs of the cell.